Решите уравнение : 4(х-1)-3(х+2)=6

Найдите корни уравнения : (3х+8)(8х-1)=0

Упростите уравнение : 2(3х-1)-4(2х+3)

2

Ответы и объяснения

2013-05-17T15:39:30+04:00
1) 4x-4-3x-6=6
4x-3x=4+6+6
x=16
2) 24x^2-3x+64x-8=0
24x^2+61-8=0
Через дискриминант сам распиши...
В итоге:
x1=1/8
x2=16/6 или 2 целых 4 десятых.
3) 6x-2-8x-12=0
-2x-14=0
-2x=14
x=-7
Лучший Ответ!
2013-05-17T15:42:16+04:00

4(х-1)-3(х+2)=6

4x-4-3x-6-6=0

x-4-6-6=0

x-10-6=0

x=16

 

(3х+8)(8х-1)=0

24x^2+61x-8=0

D=61^2-4*24*(-8)=3721+768=4489

x1=(67-61)/(2*24)=6/48=0.125
x2=(-67-61)/(2*24)=-8/3

 

или

 

3х+8=0

x=-8/3

8х-1=0

x=1/8

x=0.125

 

2(3х-1)-4(2х+3)=6x-2-8x-12=-2x-14